2016
DOI: 10.1109/tr.2016.2608910
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Impact Analysis and Access Reliability Enhancement for 1T1MTJ STT-RAM

Abstract: Spin-Transfer Torque Magnetic Random Access Memory (STT-RAM) is a promising and emerging technology due to its many advantageous features such as scalability, nonvolatility, density, endurance and fast access speed. However, the operation of STT-RAM is severely affected by environmental factors such as process variations and temperature. As the temperature rockets up in modern computing systems, it is highly desirable to understand thermal impact on STT-RAM operations and reliability. In this paper, a thermal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 38 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…This paper focuses on the thermal behaviors of the MTJ device. There are many works on studying the switching behaviors of MTJ device under the temperature variations, but an electrical model capturing the thermal properties of the MTJ device is still missing for circuit design and evaluation [17,18]. In this paper, we first present a compact MTJ model that includes the thermal properties.…”
Section: Thermal Issues Of Stt-mrammentioning
confidence: 99%
“…This paper focuses on the thermal behaviors of the MTJ device. There are many works on studying the switching behaviors of MTJ device under the temperature variations, but an electrical model capturing the thermal properties of the MTJ device is still missing for circuit design and evaluation [17,18]. In this paper, we first present a compact MTJ model that includes the thermal properties.…”
Section: Thermal Issues Of Stt-mrammentioning
confidence: 99%
“…Especially, the characteristics of FM materials, such as TMR, are very sensitive to environmental temperature, which has already been observed in many experiments, such as in [87]. Wu et al [88] proposed a thermal model of MTJ validated by published experimental measurements and found a significant read disturbance in the deep submicrometer regime. A bodybiased feedback sensing amplifier was also proposed to improve read reliability at high temperatures.…”
Section: A Reliability Modeling and Evaluation Methodologies Of Mrammentioning
confidence: 87%
“…Moreover, the resistance distributions of the STT-MRAM cell are also affected by the working temperature. It has been found that with the increase of temperature, the high resistance R 1 will decrease and while the low resistance R 0 hardly changes [5]. Fig.…”
Section: Channel Modelmentioning
confidence: 93%
“…In the recently commercialized STT-MRAM, the change of the working temperature also has a significant impact on the memory reliability. In particular, with the increase of temperature, the low resistance of the STT-MRAM cell hardly changes, but the high resistance decreases, thus leading to more overlapping of the memory resistance distributions [5]. The corresponding deviations from the nominal values of memory readback signals (e.g.…”
Section: Introductionmentioning
confidence: 99%